2021
DOI: 10.4103/jpbs.jpbs_829_20
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Psychological Effect on Undergraduate/ Postgraduate Students in Lockdown COVID-19 Situation

Abstract: Background: Student psychological health has been an increasing concern. The COVID-19 pandemic situation has brought this vulnerable population into renewed focus. Objective: Our study aims to conduct a timely assessment of the effects of the COVID-19 pandemic on the mental health of college graduates and postgraduates. Methodology: We conducted online survey with 550 students to understand the effects of the pandemic on their psychology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Due to taking online classes during the pandemic, several students acknowledged experiencing mental health problems. Verma et al's (2021) study found that 97% of the students were impacted by the lockdown. According to Pramukti et al (2020), factors linked with high levels of anxiety varied across nations, with Thai students having the greatest levels of anxiety.…”
Section: Online Class and Mental Healthmentioning
confidence: 96%
See 1 more Smart Citation
“…Due to taking online classes during the pandemic, several students acknowledged experiencing mental health problems. Verma et al's (2021) study found that 97% of the students were impacted by the lockdown. According to Pramukti et al (2020), factors linked with high levels of anxiety varied across nations, with Thai students having the greatest levels of anxiety.…”
Section: Online Class and Mental Healthmentioning
confidence: 96%
“…Many individuals relied on online interaction to fulfill fundamental requirements including interacting with others, getting access to food and medical care, working, and fulfilling other duties. Anxiety, sadness, stress, and obsessive-compulsive disorder are just a few of the psychological and mental health issues that regular internet use has been linked to, according to research by Verma et al (2021). It's because people have become so reliant on the internet for fundamental requirements that they have forgotten how to interact with friends and family.…”
Section: Internet Addiction and Mental Healthmentioning
confidence: 99%
“…Students were left with concern and uncertainty surrounding their health, mental health, and academic future. Furthermore, many students had trouble adjusting to online learning (Verma et al., 2021) and could no longer turn to social activities as a form of socioemotional coping (Tasso et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Health condition of college students may be more vulnerable during the online learning period due to the lockdowns [21]. Therefore, it is of particular urgency and importance to draw attention to both mental and oral health in this population.…”
Section: Introductionmentioning
confidence: 99%